IMPLEMENTASI LANDASAN LAYANAN BK DALAM KEBERMAKNAANNYA DI SEKOLAH - Rifmasari, Yessi; Neviyarni, Neviyarni (Jurnal Ilmiah Aquinas, 2023)
The research was conducted to find the implementation of guidance and counseling services in elementary schools. The method used is descriptive qualitative. Data was collected through three activities, namely interviews, observation, documentation. The results of this study indicate planning and implementation. The research was carried out in three activity cycles. The results of the study show 1) guidance services can be carried out by analyzing the needs of students, 2) the need for collaboration between parents and schools regarding guidance and counseling provided to students, 3) supervising teachers observe students' responses to the guidance and counseling services provided. Furthermore, the teacher observes changes in students which can be seen from the achievement of the goals of guidance and counseling services, the achievement of developmental tasks, learning outcomes, and the success of students after graduating from school both in further studies and life in society.